Perbedaan Efektivitas Lama Pemberian Rose Effleurage terhadap Intensitas Nyeri Kala I Fase Aktif pada Persalinan Normal Primigravida di Kota Semarang Tahun 2013 - Rachmitha Nur Utami (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
Pain is a reason of psycological stress on delivery mothers. This feeling that occur during labour may cause both stress which increase the adrenalin secretion and also prolonged labour. Rose effleurage is a therapy to decrease pain during labour. It is combining benefits of aromatherapy and massage. The aim of this research was to identify effectiveness difference of rose effleurage duration to pain intencity during active phase stage I normal labour primigravida in Semarang City 2013. This research used pretest- posttest non-equivalen group design. The sampling techniques had been used was purposive sampling. Pain intencity mea-surement was observed to twenty primigravida delivery mothers. The measuring instrument had been used was numeric scale. The data were analized quantitatively by Paired T- Test. The result showed the comparison of mean (Me) and standard deviation (SD) twenty minutes rose effleurage 7,2 ± 1,03 was lower than mean (Me) and standard deviation (SD) ten minutes rose effleurage 7,7 ± 0,95 so that twenty minutes rose effleurage is more effective than ten minutes rose effleurage. Rose effleurage can be applied in midwifery care to reduce pain intencity during labour at least minimal twenty minutes treatment.